Analysis of Condominium Occupants Satisfaction Post Rebuilding - Sugeng Hariyanto; Farida Hardaningrum (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2022)
The increase in population in Surabaya is increasing which results in the need for housing also increasing. Therefore, the Surabaya City Government strives to provide decent housing for the community through the construction of rental flats, one of which is the Sombo Flats located on Jl. Sombo, Simolawang Village, Simokerto District, Surabaya City. In 2020, damage to the Sombo Flats Block E began to appear, so the Surabaya City Government carried out demolition and rebuilding. This study aims to determine the level of satisfaction of the residents of the Sombo Flats Blok E after the rebuilding. This type of research is quantitative research with a cross-sectional approach . The number of samples in this study were 50 heads of families. The analytical method used is descriptive statistical analysis and multiple regression analysis. The result of this research is that the occupants of the sombo flats block E feel a moderate level of satisfaction . This shows that the majority of sombo flats block E customers are quite satisfied with the rental rates of the flats, the management of the flats, the quality of the flats, the completeness of the facilities and infrastructure of the flats, the arrangement of the flats and are quite satisfied based on the overall Occupant Satisfaction variable. Meanwhile , the factors that most influence the satisfaction of the residents of the Sombo Flats are the quality of the flats and the spatial arrangement of the flats.